Protein production and purification. - Gräslund, S; Nordlund, P; Weigelt, J; Hallberg, B; Bray, J; Gileadi, O; Knapp, S; Oppermann, U; Arrowsmith, C; Hui, R; Ming, J; dhe-Paganon, S; et al. (2008)
In selecting a method to produce a recombinant protein, a researcher is faced with a bewildering array of choices as to where to start. To facilitate decision-making, we describe a consensus 'what to try first' strategy based on our collective analysis of the expression and purification of over 10,000 different proteins. This review presents methods that could be applied at the outset of any project, a prioritized list of alternate strategies and a list of pitfalls that trip many new investigators.